Frog and beaver - James, Simon, 1961- (Somerville, Massachusetts : Candlewick Press, 2018)
A charming ecological fable of community and friendship from award-winning author-illustrator Simon James. Frog and his friends all live happily together on the river. At least they do until Beaver comes along. Beaver is determined to build the biggest and best dam that anyone has ever seen, but it's so big that it stops all the water and Frog and his friends are forced to move. Frog tries to warn Beaver that his dam is too big, but busy Beaver just won't listen.
003+.
Keywords: Frogs -- Juvenile fiction; Stream animals -- Juvenile fiction; Beavers -- Juvenile fiction; Dams -- Juvenile fiction; Environmental protection -- Juvenile fiction; Habitat conservation -- Juvenile fiction; Frogs -- Fiction; Beavers -- Fiction; Dams -- Fiction; Fiction; Juvenile works; Picture books; Picture books